THE USE OF ANIMATION VIDEO AS LEARNING MEDIA FOR YOUNG LEARNERS TO IMPROVE EFL STUDENTS' MOTIVATION IN LEARNING ENGLISH - Ni Komang Prasetyani Laksmi; I Kadek Anggardana Yasa; Kadek Ayu Mas Mirayani (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
Currently, the use of learning media has an essential role in the educational field. Students and teachers have used the implementation of media in the classroom. The performance of media in the academic field is limited to adult learners and young learners. One of the media commonly used in the learning process is the Animation Video, such as the Pow Toon Animation Video. The implementation of Animation Video in the classroom brings several perceptions toward students. This study was designed using the library research method. Therefore, this paper aims to share some theoretical concepts and pedagogical practices using Animation video towards the young learners' perceptions.